Pengaruh Pengaruh Person Organization Fit, Person Job Fit dan Instrinsic Motivation Terhadap Job Satisfaction Pada Karyawan - Apriano Rinaldo Putra; Syofian; Sintia Safrianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Human resource management has an important role in fulfilling the smooth running of activities in an organization. Organizations that are driven by human resources must have the same specifications as the needs of the organization, so as to increase the efficiency and effectiveness of carrying out tasks in order to achieve organizational goals. For this reason, human resource management must look for factors that can encourage job satisfaction from their employees. The following factors that are thought to have an influence on employee job satisfaction are person organization, person job fit, and intrinsic motivation. The method used in this research is descriptive quantitative approach (explanatory research). The population in this study were all employees at the Grage Resort Bengkulu hotel and the sample used in this study totaled 59 people. The sampling technique (sampling) in this study using total sampling. Data analysis in this study was using the t test (Partial Coefficient Test), f test (Joint Regression Coefficient Test) and the coefficient of determination test with a significance level. The results showed that the significant value of the f test results between Variable X1 (Person Organization Fit) has a significant value of 0.001, so 0.001 ≤ 0.05 means that X1 has a significant effect on Y. X2 (Person Job Fit) has a significant value of 0.000, therefore 0.001 ≤ 0.05, this means that X2 has a significant influence on Y. And (Intrinsic Motivation) on Y (Job Satisfaction has a significant value of 0.072, therefore 0.001 ≥ 0.05, this means that X3 on Y does not have a significant effect. Therefore X1, X2 and X3 on Y have a significant effect. So that the results of the hypothesis in this research is that there is a significant influence between Person Job Fit and Person Organization Fit at Hotel Grage Resort Bengkulu.